Experience in the treatment of psoriasis patients using Apremilast, a selective signalling pathway inhibitor - N. V. Kungurov; N. V. Zilberberg; M. M. Kokhan; J. V. Keniksfest; E. V. Grishaeva (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
The article presents a brief description of Аpremilast - the target synthetic anti-inflammatory drug, which is representative of a new class of agents for the treatment of psoriasis and psoriatic arthritis. The efficiency and safety of the new drug in the treatment of patients with severe psoriasis are shown.